High Order Thingking Skill dalam Pengembangan Perangkat Pembelajaran Akuntansi dengan Model Problem Based Learning - Ismi Solikhatun (Edunusa: Journal of Economics and Business Education, 2022)
This study aims to determining the validity of developing learning tools with Problem-Based Learning consisting of lesson plans and evaluation instruments consisting of basic competencies of analyzing the recording of merchandise sales transactions on credit, money orders and installment sale. The learning tools developed consist of lesson plans, learning instruction, and learning evaluations for learning high order thinking skills with the Problem-Based Learning Models. The results show that 1) The lesson plan used in learning activities is declared valid, 2) the learning instruction used in learning have been validated and declared valid with a very appropriate category, 3) evaluation of learning used to find solutions to improve and increase student self-confidence with PBL also declared valid with a very decent category.